2012
DOI: 10.1590/s0102-695x2012005000102
|View full text |Cite
|
Sign up to set email alerts
|

In vitro isoflavonoid production and analysis in natural tetraploid Trifolium pratense (red clover) calluses

Abstract: Isoflavones are polyphenolic phytoestrogens, predominantly found in leguminous plants. Trifolium pratense L., Fabaceae (red clover), is rich in isoflavones that possess estrogenic activity due to their similar molecular structure and effectiveness in preventing health conditions such as menopause, osteoporosis, cardiovascular disease, hypertension and hormone-dependent cancers. In this study, presence and amount of various phytoestrogens in the tetraploid plant and in the calluses derived from the plants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
2
1
0
Order By: Relevance
“…Kasparová et al (2006) used Gamborg medium for callus and suspension cultures in 4 different diploid varieties of T. pratense L. As a result, TLC and HPLC only detected formononetin. Our results were in accord with the previous study (Ercetin et al, 2012) in terms of formononetin and genistein production in callus culture with Gamborg B5 medium. In conclusion, a cell suspension culture method was developed for M. sativa L. 'Elçi' , in which daidzein and formononetin were produced in as little as 18 days.…”
Section: Discussionsupporting
confidence: 93%
“…Kasparová et al (2006) used Gamborg medium for callus and suspension cultures in 4 different diploid varieties of T. pratense L. As a result, TLC and HPLC only detected formononetin. Our results were in accord with the previous study (Ercetin et al, 2012) in terms of formononetin and genistein production in callus culture with Gamborg B5 medium. In conclusion, a cell suspension culture method was developed for M. sativa L. 'Elçi' , in which daidzein and formononetin were produced in as little as 18 days.…”
Section: Discussionsupporting
confidence: 93%
“…In the present investigation Chloroform: methanol (8:2) combination showed best results and exhibited coherence with the results of [13,14]. HPTLC technique with other biochemical assays supplemented evidence to confirm the presence of some bioactive compounds, which have provided the plants an important position in folkloric usage [15] In the present study, quantitative and qualitative biochemical methods can be employed as a stability indicator [16] that can be used for the routine quality control analysis and quantitative determination of β-sitosterol from Lepidium sativum.…”
Section: Discussionsupporting
confidence: 87%
“…The content of these compounds varies greatly depending on different factors. However, the majority of studies found that formononetin and biochanin A are the dominant isoflavones in red clover [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. In this study, concentrations of formononetin were in ranges of 0.22–4.68 mg/g, 0–0.95 mg/g and 0.10–1.54 mg/g in leaves, flowers and stems, respectively, while these values for biochanin A were 0.59–5.94 mg/g, 0.17–1.52 mg/g and 0.08–0.56 mg/g ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%